An effective algorithm for mining closed sequential patterns and their minimal generators based on prefix trees. (1st January 2013) - Pham, Thi-Thiet; Luo, Jiawei; Vo, Bay
Sequential generator patterns and closed sequential patterns play an important role in data mining tasks. They are proposed to address difficult problems in mining sequential pattern and have often been used together to generate non-redundant rules. Based on their important role, this paper proposes an efficient algorithm called CloGen for mining closed sequential patterns and their minimal sequential generator patterns. The CloGen algorithm uses the parent-child relationship on prefix tree structure and inserts fields into each node on prefix tree to determine whether that is a minimal sequential generator pattern or closed sequential pattern. Experimental results show that the performance runtime of CloGen algorithm is much faster than that of other algorithms by more than one order of magnitude.